Discrimination of Smoke-Exposed Pinot Noir Wines by Volatile Phenols and Volatile Phenol-Glycosides - Armando Alcazar-Magana; Ruiwen Yang; Michael C. Qian; Yanping L. Qian (Molecules)
This study investigated the correlation between five primary volatile phenols (VPs) and their glycosides in smoke-exposed and non-smoke-exposed Pinot noir wines to assess and identify potential markers for smoke taint. The results showed that all putative VP-glycosides in smoke-exposed wines were higher than in non-smoke-exposed wines, with a fold change ranging from 2.11 to 31.88 for the top fifteen differentiations. VP-glycosides showed strong positive correlations among themselves, with correlation coefficients of 0.94 for hexose-guaiacol vs. pentose (P)-hexose (H)-cresol and 0.92 for syringyl-β-D-glucopyranoside vs. H-P-4-methylguaiacol. VP-glycosides also showed relatively high correlations with free and strong acid-hydrolyzed VPs. The correlation coefficient between H-P-guaiacol and free-form guaiacol is 0.71, and between H-P-guaiacol and total guaiacol is 0.78. The strong correlation suggests that these compounds are interconnected and regulated by the severity of smoke exposure. Multivariate analysis effectively differentiated smoke-exposed wines from non-smoke-exposed ones. However, more research is needed to fill the gaps in understanding smoke-derived compounds.